ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI (PERIODE 2015-2017) - Camelia Verahastuti, Nur Hasanah, H. Eddy Soegiarto K (EKONOMIA, 2020)
Textile and garment companies that are the object of research is PT Indo Rama Synthetics Tbk, PT Pan Brothers Tbk, PT Ricky Putra Globalindo Tbk, PT Star Petrochem Tbk, PT Trisula Internasional Tbk dan PT Nusantara Inti Corpora Tbk. The analysis technique used are current ratio, quick ratio, debt to assets ratio, debt to equity ratio, return on assets and return on equity. The date used is the companies financial statement in 2015-2017.The theory of this research is that financial management focuses on financial ratio analysis using 3 ratios, namely liquidity ratios, solvency ratios and profitability ratios. This study uses a descriptive method in which the authors describe the financial performance of textile and garment companies listed for period 2015, 2016, 2017.The results showed : 1) The liquidity ratio in the current ratio and quick ratio has increased from year to year, seen from the industry average, PT Pan Brothers Tbk has the best performance in terms of liquidity ratios compared to other companies. 2) Solvability ratio on debt to assets ratio and debt to equity ratio fluctuate from year to year, seen from the industry average, PT Star Petrochem Tbk has the best performance in terms of solvency ratio compared to other companies. 3) Profitability ratios on return on assets and return on equity have decreased from year to year, seen from the industry average, PT Trisula Internasional Tbk has the best performance in terms of profitability ratios compared to other companies